Prevalence and Variations of Sesamoid Bones in the Hands of Patients Visiting Teaching Hospital of Kaski District: A Retrospective Study - Singh, Sushma; Sharma, Pujan; Sharma, Bhoj Raj; Barnawal, Kanchan Kumari (Journal of College of Medical Sciences-Nepal, 2023)
Introduction: Sesamoids are small, well-corticated, ovoid or nodular, may be bipartite ormultipartite bones/ossifications found close to a bone or a joint that are subject to significant morphological variations. Although it is difficult to determine the symptomatic nature of these bones, imaging provides important diagnostic information. The objective of this study is to assess the prevalence and variations of sesamoid bone in hands of patients visiting a teaching hospital of Kaski district. Methods: A hospital based retrospective cross-sectional study was conducted by analyzing X-rays of hand with Anteroposterior (AP) view, a total of 150 both male and female patients between the age group of 18 to 85 wereimaged between August 1, 2022 to December 30, 2022 at Department of Radiology & Imaging(X-Ray Unit). Presence of sesamoid bone of hand was noted on 1st, 2nd, 3rd, 4th and 5th metacarpophalangeal joints (MCPj), and the 1st interphalangeal joint (IPj), separately. The data were analyzed for correlation using Pearson’s correlation test. Ethical approval was taken from the Institutional Review Committee of Gandaki Medical College (Reference No.159/079/080). Results: The prevalence of sesamoid bone at 1st, 2nd, 3rd, 4th and 5th MCPj, and 1st IPj were 100 (100%), 60 (46%), 24(16%), 20(13.3%), 100(66.7%), and 114(76%) respectively. Variation was more prominent among females at 2nd, 3rdand 5th MCPj and 1st IPj, Also, SB variation was more prominent on left hand compared to right hand in 2nd, 4thand 5th MCPj and 1st IPj. Conclusions:No significant correlation between the gender and laterality with presence or absence of SB in the hands were noted.